Nanominerals, Mineral Nanoparticles, and Earth Systems - Hochella, Michael F.; Lower, Steven K.; Maurice, Patricia A.; Penn, R. Lee; Sahai, Nita; Sparks, Donald L.; Twining, Benjamin S. (Science (American Association for the Advancement of Science), 2008)
Minerals are more complex than previously thought because of the discovery that their chemical properties vary as a function of particle size when smaller, in at least one dimension, than a few nanometers, to perhaps as much as several tens of nanometers. These variations are most likely due, at least in part, to differences in surface and near-surface atomic structure, as well as crystal shape and surface topography as a function of size in this smallest of size regimes. It has now been established that these variations may make a difference in important geochemical and biogeochemical reactions and kinetics. This recognition is broadening and enriching our view of how minerals influence the hydrosphere, pedosphere, biosphere, and atmosphere.